Common Agricultural Policy in the EU and the Ministry of Agriculture in the Czech Republic with a Focus on Environmental and Consumer Protection and Support for Smes - Jurčík Radek (EU agrarian Law)
The common agricultural policy and the implementation of this policy represent a relatively high part of the costs in the EU budget. From this point of view, the content of the common agricultural policy is important to meet both the primary objective (production of agricultural products) and the secondary objectives (sustainable development, soil protection, consumer and environmental protection).